2017
DOI: 10.21037/atm.2017.02.33
|View full text |Cite
|
Sign up to set email alerts
|

The effect of financial crisis on the profile of the patients examined at the surgical emergencies of an academic institution in Greece

Abstract: Financial crisis seems to have a multivariable effect on epidemiology and clinical diversity of patients being examined in the ER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…EDs offer whole-day, free of charge, preventive, curative services responsive to emergencies as well as rehabilitation services—mainly to urban and semi-urban populations [ 27 ]. On the other hand, in primary care facilities, uninsured patients have to pay their medical bills for most care visits.…”
Section: Impact Of the Economic Recession On Ems Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDs offer whole-day, free of charge, preventive, curative services responsive to emergencies as well as rehabilitation services—mainly to urban and semi-urban populations [ 27 ]. On the other hand, in primary care facilities, uninsured patients have to pay their medical bills for most care visits.…”
Section: Impact Of the Economic Recession On Ems Functionmentioning
confidence: 99%
“…This increase is exacerbated by a hospital’s organisational problems, for instance, shortages of staff, laboratory, and admission delays. Accordingly, an ED becomes overcrowded, with inevitable consequences [ 14 , 27 , 30 ]. However, the extent of the workload currently has not been thoroughly evaluated in Greece, as patient data are not regularly recorded.…”
Section: Impact Of the Economic Recession On Ems Functionmentioning
confidence: 99%
“…Recent literature has shown that the number of the patients seeking medical help during the crisis has increased while their profile and reason for attendance has shifted (4). The effects on public and private Healthcare sectors should be different due to the different funding resources and probably due to different socio-economic populations they might serve.…”
Section: Introductionmentioning
confidence: 99%